Pengaruh Kemudahan Dan Kepercayaan Terhadap Minat Penggunaan Qris Sebagai Pembayaran Digital Pada Pelaku Usaha Kecil Di Kecamatan Binawidya Kota Pekanbaru - Welly Harlianti; Mujiono Mujiono; RM. Riadi (Rashid : Journal of Economic, 2026)
This study aimed to examine the effect of perceived ease of use and trust on the intention to use Quick Response Code Indonesian Standard (QRIS) as a digital payment method among small business owners in Binawidya District, Pekanbaru City. This research employed a quantitative approach with a descriptive method. The population consisted of 102 small business owners, while 50 respondents were selected using the Slovin formula and purposive sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS. The findings revealed that perceived ease of use had a positive and significant effect on the intention to use QRIS. Trust also had a positive and significant effect on QRIS usage intention. Simultaneously, perceived ease of use and trust significantly influenced the intention to use QRIS. These findings indicate that the higher the perception of ease and trust toward QRIS, the greater the intention of small business owners to adopt QRIS in their business transactions.